2014
DOI: 10.3892/or_xxxxxxxx
|View full text |Cite
|
Sign up to set email alerts
|

Matrine alters microRNA expression profiles in SGC-7901 human gastric cancer cells

Abstract: Matrine, a major alkaloid extracted from Sophora flavescens, has been reported to possess antitumor properties in several types of cancers, including gastric cancer. However, its mechanisms of action on gastric cancer remain poorly understood. Dysregulation of microRNAs, a class of small, non-coding, regulatory RNA molecules involved in gene expression, is strongly correlated with cancer. The aim of the present study was to demonstrate that matrine treatment altered miRNA expression in SGC7901 cells. Using miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Acting as oncogenes or tumor suppressors, miRNAs can repress the expression of cancer-related genes (16). Several studies have reported that alterations in miRNA levels occur in various human tumors, including GC, where miRNAs are related to several aspects of cancer pathogenesis including self-renewal, invasion and metastasis by targeting EGR2 (17), MAPk (18) and PI3k/AkT signaling pathways (19). Therefore, we speculate that specific miRNAs may participate in the regulation of EGFR protein expression in GC.…”
Section: Introductionmentioning
confidence: 90%
“…Acting as oncogenes or tumor suppressors, miRNAs can repress the expression of cancer-related genes (16). Several studies have reported that alterations in miRNA levels occur in various human tumors, including GC, where miRNAs are related to several aspects of cancer pathogenesis including self-renewal, invasion and metastasis by targeting EGR2 (17), MAPk (18) and PI3k/AkT signaling pathways (19). Therefore, we speculate that specific miRNAs may participate in the regulation of EGFR protein expression in GC.…”
Section: Introductionmentioning
confidence: 90%
“…MicroRNAs (miRNAs/miRs) are considered to have important roles in tumors. It has recently been reported that matrine alters miRNA expression profiles in SGC-7901 human gastric cancer cells, providing a novel and promising approach to identify the mechanisms of action of matrine (18). In this study, an miRNA microarray was used to screen relative miRNA levels of SGC-7901 human gastric cancer cells following matrine treatment (18).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses showed that E2F-1 and Apaf-1 were upregulated and that caspase-9 and -3 were activated after the exposure to matrine [21] . Li et al [22] identified 128 miRNAs exhibiting >2-fold expression changes in matrine-treated cells relative to their expression levels in untreated cells. The data revealed that the majority of the 57 identified enrichment pathways were highly involved in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%